Seerah, Human Rights, & Women’s Dignity: Exploring Concepts of Equality & Justice in Islam & Addressing Violence against Women - Abdul Qayyum Gondal; Prof. Dr. Matloob Ahmad*; Dr. Anum Hameed (Al-Amīr Research Journal for Islamic Studies, 2024)
The Seerah, which recounts the life and deeds of the Prophet Muhammaﷺ, is an invaluable resource for learning about the early Islamic ideals of equality and social justice. An analysis of these concepts’ relevance to women’s rights protection and gender equality is the basis of this inquiry. This research attempts to show how Islam has been a torchbearer of human dignity in general and women’s rights in particular by analyzing the Seerah from historical and moral perspectives. It also aims to reintroduce these fundamental ideas into the continuing discussions around violence against women by demonstrating the relevance of previous struggles for justice and fairness to the problems of the present. A multi-method approach is used in the research to examine the interconnections between humans. This study considers how these principles might potentially solve ongoing challenges related to female violence by outlining how they should be applied while taking historical circumstances and Islamic law into account. It reveals that although the overarching goal of Islamic theology is equality and justice, its ancient story is vulnerable to contemporary circumstances. To eradicate violence against women, reform consideration is necessary in every situation as women’s whole dignity and a just and equal life expectancy are at risk. Keywords: Social justice, seerah, women’s dignity, violence against women, gender equity, human rights, women’s status in Islam, Islamic teaching, Historical context of gender bias.